ANALISIS KALIMAT IMPERATIF PADA SPANDUK PARTAI POLITIK MENUJU PEMILU 2024 DI KOTA SURAKARTA - Sindhu Linguistika Manumasa; Habib A K; Sumarlam Sumarlam (Universitas Sebelas Maret, 2024)
The purpose of the research is to describe the types and functions of imperative sentences on political party banners towards the 2024 election in Surakarta City. This research uses descriptive qualitative method. The object is imperative sentences, the data used are imperative sentences on banners along with their contexts and the main data sources used are political party banners towards the 2024 elections in the city of Surakarta. The objects are imperative sentences, the data used are imperative sentences on banners along with their contexts and the data sources are written documents of political party banners towards the 2024 elections in Surakarta City. Data collection is done by data source triangulation technique and data collection method triangulation technique. The data source triangulation technique is used to check data from various sources. The method of observation is done by directly observing the object of research, namely imperative sentences on political party banners towards the 2024 elections in Surakarta City. Documentation is used to document political party banners in Surakarta City by photographing them to facilitate the data collection process. This technique is used to record or classify the data according to the types of imperative sentences. The results of this study found imperative sentences with the types, (1) prohibition, (2) order, (3) ordinary, (4) command, (5) request and (6) invitation. The functions of imperative sentences found are (1) the function of conveying a signal, (2) the function of inviting, (3) the function of commanding, (4) the function of requesting and (5) the function of prohibiting